A ascensão política de José Mujica no Uruguai: de guerrilheiro tupamaro a presidente da República - Ferrari, Dércio Fernando Moraes (2016)
The Movement of National Liberation-Tupamaros (MLN-T) emerged in the pre-dictatorship and was suppressed during that period, leading the F.A. to the illegality, who had arrived to the Uruguayan presidency in 2005, with Tabaré Vázquez. Mujica, who was in jail during 13 years during the dictatorship, began his political journey as congressman in 1994, was senator in 1999, Minister of Agriculture in 2005 and President of the Republic between 2010-2015. His rise to power represented an increase in rupture with the tradition bipartisan and gave strength to the left in the country, once during his government were created public policies who received worldwide attention, as the decriminalization of abortion and the regulation of marijuana, bringing the country and the president to the center of the international media. These and other measures provide to Mujica and Uruguay his own great media visibility as in any other period in the country history, making the "periphery" the "center of the world." As described, this research pursuit to analyze the José Mujica climbing in the Uruguayan policy, from 1970, in tupamara militancy, until his election as president in 2009. In this direction, the objective of this research is even analyzing the factors who had contributed to the attention who Mujica received by the media during his time as Uruguayan representative.